The effects of denervation and formoterol administration on facial growth - Fitzpatrick Brendan; Woods Michael; Lynch Gordon; Manton David (Sciendo, 2014)
Objective: To identify and demonstrate possible alterations of skeletal structures which might follow either unilateral surgical denervation of the masseter muscle, unilateral intramuscular injection of formoterol directly into the masseter muscle, or intramuscular formoterol injection after surgical denervation.